IOT Security Challenges and Measures to Mitigate: Novel Perspectives - Kumar Yogi, Manas; Himatej, Y; Mahesh reddy, M (International Journal of Engineering and Technology, 2018)
The Internet Of Things describes the ever-growing number of intelligent objects that are being connected to the internet and each other, smartphones, tablets, wearable technology and smart home devices are adopted into our everyday lives. The security of IOT is becoming more complex and may have a serious consequence. So, now we have many security challenges like privacy concerns, routine cryptography, passive data collection etc. Many people hide personal data in social media to eliminate these sort of privacy issues but common man nowadays is becoming a passive participant due to lack of security in these IOT devices that are surrounding us.